Development of Mathematics Learning Model Based on Mapalus Values: Efforts to Improve Mathematical Literacy and Students' Social Skills - Domu, Ichdar; Mangelep, Navel Oktaviandy (Journal of Cultural Analysis and Social Change, 2025)
Mathematics learning in Indonesia still faces serious challenges due to the dominance of conventional methods that make students passive and difficult to relate concepts to real life. This research aims to develop and test the effectiveness of the macarmatic learning model based on Mapamus values, which is a typical Minahasa gotong royong tradition, in improving learning outcomes, engagement, and motivation of junior high school students. The research uses a research and development approach with the stages of needs analysis, prototype design, expert validation, limited trials, and model revision. The trial was carried out in two classes VII of junior high school (N=60) which were divided into an experimental class with the Mapalus model and a control class with the conventional method. The research instruments included learning outcome tests, engagement observation sheets, perception questionnaires, and interviews with teachers and students. The results showed that the Mapalus model was valid with an average score of 3.6 from expert validation. Quantitatively, students in the experimental class achieved a significant improvement with an average posttest of 78.4 and an N-gain of 0.53 (medium-high category), while the control class only achieved an average of 65.1 with an N-gain of 0.25 (low category). Observations showed that the involvement of the students of the experimental class increased from 52% at the first meeting to 83% at the fourth meeting, while the control class was stagnant at 41–44%. Questionnaire and interview data confirmed that students felt more motivated, confident, and found the material more relevant to daily life. This research confirms that the integration of local cultural values through the Mapalus model not only improves mathematical understanding, but also fosters collaborative character, empathy, and responsibility. These findings have important implications for the development of culture-based learning in line with the Independent Curriculum and the strengthening of the Pancasila Student Profile.